STRATEGI PENINGKATAN DAYA SAING USAHA PRODUKSI ROTI PADA SKALA RUMAH TANGGA (Studi Kasus Rosana Bakery Desa Buruan, Kecamatan Penebel, Kabupaten Tabanan, Bali) - Rai Safitri, Ni Made; Wiranatha, Agung Suryawan; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 3 (2017): September, 2017)
The objectives of this study were to calculate the added value of bread production, to analyze the internal and external conditions and to formulate strategies and to set priority strategy to increase the competitiveness of bread production at Rosana Bakery. Analysis was undertaken by using value added analysis of the modified Hayami method. The results showed that the value added one packet for Donut was Rp. 265.22, Roti Manis was Rp. 226.51 and Roti Sobek was Rp. 1,572.67. Analysis of strategies of enhancing business competitiveness was under taken by using SWOT matrix, supported by quantitative analysis by using matrix EFE, IFE, IE and QSPM. The result showed that the weighted value for the matrix Internal Factor Evaluation (IFE) was 3.00 (strong position) the External Factor Evaluation (EFE) was 2.64 (medium position). In the matrix Intternal External (IE) strategy that must be done was grow and establish strategies (growth and build), which consists of intensive strategies (market penetration, market development and product development) or integrative strategies (blackward integration, forward integration and horizontal integration). There are eight alternative strategies can be drawn up to develop the business competitiveness of Rosana Bakery. The highest TAS value of existing alternative strategies are to enhance product maketing effrts through intensive and efficient promotion and increase product quantity. Key words: bread, value added, SWOT, QSPM